2010
DOI: 10.1200/jco.2009.25.6636
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Predictors of Missed Opportunities in Lung Cancer Diagnosis: An Electronic Health Record–Based Study

Abstract: Preventable delays in lung cancer diagnosis arose mostly from failure to recognize documented abnormal imaging results and failure to complete key diagnostic procedures in a timely manner. Potential solutions include EHR-based strategies to improve recognition of abnormal imaging and track patients with suspected cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 49 publications
4
99
0
Order By: Relevance
“…The magnitude of this category is in the high range compared to previous reports. 33 In accordance with other findings [15][16][17] it was found that the diagnostic pathway is suboptimal for some patients in general practice, which suggests that more focus is needed on patients with negative test results.…”
Section: Ethical Approvalsupporting
confidence: 88%
See 1 more Smart Citation
“…The magnitude of this category is in the high range compared to previous reports. 33 In accordance with other findings [15][16][17] it was found that the diagnostic pathway is suboptimal for some patients in general practice, which suggests that more focus is needed on patients with negative test results.…”
Section: Ethical Approvalsupporting
confidence: 88%
“…10 A quality deviation (QD) can, in general practice, functionally be defined as 'an event that should not have happened and that you do not want to happen again', 11 as no harm to the patient is reported in up to 60% of QDs in general practice. 13,14 Most studies on QDs in cancer diagnosis are based on retrospective audits of clinical data 15,16 or patient questionnaires 17 and…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, when the initial diagnosis is incorrect or initial management misguided, prompt follow-up is often the only way the error can be recognized and corrected. [2][3][4]6 Despite the importance of close followup, much remains to be done to improve the process of outpatient follow-up care.…”
mentioning
confidence: 99%
“…Suboptimal follow-up may be associated with adverse events and poor patient outcomes. [2][3][4][5] Ensuring timely patient follow-up is essential when a diagnosis or treatment plan is uncertain, or when there is a specific need to closely monitor a patient's condition. Additionally, when the initial diagnosis is incorrect or initial management misguided, prompt follow-up is often the only way the error can be recognized and corrected.…”
mentioning
confidence: 99%
“…49! of the clinical and surgical management impact (Burmeister et al, 2010;Christensen, Harvald, Jendresen, Aggresrup, & Petterson, 1997;Jensen, Mainz, & Overgaard, 2002;Koyi et al, 2002;Salomaa, Sallinen, Hiekkanen, & Liippo, 2005); one study discusses common signs and symptoms associated with the initial evaluation of lung cancer patients (Spiro, Group, & Colice, 2007); and, one study examines the characteristics of missed opportunities in the lung cancer diagnosis (Singh et al, 2010). The relevant literature that attempts to explain patient delayed help-seeking behavior in lung cancer is isolated to five studies detailed in six published articles (Corner et al, 2005;Corner et al, 2006;Leprieur et al, 2012;Lovgren et al, 2008;Tod et al, 2008;Tod & Joanne, 2010 whether symptom history and pathway toward the diagnosis differed for early stage lung cancer compared to those individuals initially diagnosed at advanced stages.…”
Section: Delay In Lung Cancermentioning
confidence: 99%